INFORMATION AND COMMUNICATION TECHNOLOGY LEARNING SYSTEM IN 21ST CENTURY EDUCATION - Yuli Supriani; Samsul Hadi; Agus Pahrudin; Yuberti; Achi Rinaldi (El Midad, 2026)
ABSTRACT This study aims to analyse the implementation of Information and Communication Technology (ICT) in 21st-century learning systems and its contribution to improving the quality of teaching and learning. The study employs a Systematic Literature Review (SLR) method to identify, evaluate, and synthesise findings from relevant national and international studies on ICT integration in education. The review indicates that ICT plays a significant role in fostering students’ 21st-century competencies, particularly the 4C skills: critical thinking, creativity, collaboration, and communication. ICT also promotes student-centred learning, increases engagement, and supports flexible and interactive instructional practices. However, its implementation remains constrained by inadequate technological infrastructure, limited internet accessibility, insufficient digital resources, and teachers’ varying levels of digital competence and pedagogical readiness. Addressing these challenges requires improved access to technology, sustainable professional development programs, and supportive educational policies. Effective and well-planned ICT integration can optimise learning outcomes, strengthen educational quality, and provide valuable directions for future research on technology-enhanced learning environments.